Cresting the commoditization curve: a regression analysis and bass diffusion model approach - Ho, Shu Xian (Nanyang Technological University, 2023)
The Bass Diffusion Model is a commonly used framework for understanding the diffusion of new products and innovations in the marketplace. In this study, Bass Diffusion Model is applied to historical data from Evoqua, a leading company in water technologies that produces water treatment systems, producing values of p = 0.00318 and q = 0.453. Similar figures of p = 0.00962 and q = 0.587 were obtained when fitted to OSEC system, which is considered a new technology. These parameters suggest that the adoption of the Onsite Sodium Hypochloride systems will be driven more by imitation than innovation, and that the majority of adoption will occur in the later stages of the diffusion process. This information can be used by the company to inform its marketing and promotion efforts, and to target both early and late adopters of the product. By leveraging the insights provided by the Bass Diffusion Model, Evoqua can mitigate the effects of commoditization and achieve sustained success in the marketplace.